An analysis of the impact of credit risk and liquidity risk on default probability in European banks - Persand-Gujadhur, Hurvashee (2014)
Credit risk is considered as the major risk in the banking industry. As such, it is one of the key factors used in estimating banks‟ probability of default (PD) and in ensuring financial stability in an economy. Liquidity risk, on the other hand, if not well-managed could pose a significant threat to the financial well-being of banks and a liquidity shortfall could hence increase banks‟ PD. This study therefore presents a model that links banks‟ PD to credit risk and liquidity risk and shows the impact that both risks have on PD through our empirical results based on a comprehensive dataset of 58 European (EU) banks during the period 2007 to 2011, which encompasses the 2007-09 financial crisis. To undertake this analysis, econometrics methodologies namely panel data regressions have been employed. Based on previous theoretical literature we observe that credit risk and liquidity risk are major predictors of bank default especially during the recent credit crunch as compared to other determinants. However, our study reveals that, unlike liquidity risk, credit risk has a statistically significant influence on banks‟ PD based on our sample of EU banks. These findings highlight the fundamental importance for new international standards on risk management, which act as a fundamental based prevention tool to avoid further bank failures.